Improvement the system of safety management in the food industry enterprises - Evtushenko, Olga; Siryk, Alina (My University, 2015)
The methods of labor protection management, based on a combination of statistical analysis, expert estimation with ranking factors and combined forecasting the risks of occupational injuries with the implementation of algorithm formation of proposals about improving working conditions in the food industry enterprises, were improved. The results, which can be used in improving the management solutions' projects about providing safe working conditions of employees in the food industry enterprises as well as in the other industries of Ukraine, were received.
Keywords: кафедра екології та екоменеджменту; safety management system; occupational injuries; safety; risk forecasting; expert evaluation factors; система управления безопасностью полетов; травматизм; безопасность; прогнозирование рисков; экспертные оценки факторов; система управління безпекою польотів; безпека; прогнозування ризиків; експертні оцінки факторів